The role of hemostatic changes in the pathogenesis of diabetic retinopathy - Preys, Nataliya; Savytskyi, Ivan (Journal of Education, Health and Sport, 2022)
Introduction: The paper presents the results of the hemostasis system of rats with experimental diabetic retinopathy. Material and methods: Experimental studies were performed on white Wistar rats, which were divided into 2 groups: 1st group – intact animals; 2nd group – 60 animals with modelling of diabetic retinopathy without correction (control pathology). Аnalysis of the hemostasis system was performed according to the following indicators: plasma recalcification time, activated partial thromboplastin time, prothrombin time, thrombin time, heparin time, thermostable thromboplastin inhibitor, thermolabile thromboplastin inhibitor and fibrinogen level. Results: Under the conditions of simulated diabetic retinopathy, the time of plasma recalcification was significantly reduced by 1.2 times (p<0.05) compared to intact rats; prothrombin time – 1.4 times (p<0.05); thrombin time – 1.1 times; heparin time – 1.1 times; thermostable thromboplastin inhibitor – 1.0 times; thermolabile thromboplastin inhibitor – 1.5 times (p<0.05), respectively. There was also a significant increase in the level of activated partial thromboplastin time by 1.3 times (p<0.05) compared to the intact group of animals and the level of fibrinogen by 4.9 times (p<0.05), respectively. Such violations of hemostasis at the initial stage of the development of diabetic retinopathy R are associated with inhibition of anticoagulation mechanisms, since the contact phase of hemocoagulation did not change significantly. On the 120th day of the experimental studies, the plasma recalcification time decreased by 1.3 times (p<0.05) compared to intact rats; prothrombin time - 1.5 times (р<0.05); thrombin time – 1.3 times (p<0.05); heparin time – 1.2 times (p<0.05); thermostable thromboplastin inhibitor - 1.1 times; thermolabile thromboplastin inhibitor - 2.0 times (p<0.05), respectively. It was established that the activated partial thromboplastin time also increased significantly by 1.4 times (p<0.05) compared to intact rats; there was a 4.0-fold increase in the concentration of fibrinogen (p<0.05), respectively, in intact animals. Conclusions: DM is characterized by a number of changes in the hemostasis system, which determine the risk of thrombotic complications. One of the main reasons for these changes is: insulin resistance, hyperinsulinemia and insufficient compensation of carbohydrate metabolism. Hypercoagulation in DR conditions is manifested by an increase in the concentration and activity of factors VII and fibrinogen.